Phosphate desorption in luvisols and solonetz from a Mediterranean region - Monteiro, M.C.H. (2010)
Transfer of P from soil to water is controlled by the P retention capacity in the solid phase, namely by the equilibrium between adsorbed and precipitated forms. Desorption of P and/or phosphate dissolution govern the amount of P released into drainage water, runoff or freshwater. Soil P evaluated by Olsen method showed a strong correlation with the capacity of soil to desorb P and, within certain limits, to the transfer of P to water. This transfer of P relates to losses that occur either in surface horizons, or in subsurface horizons (to drainage water, to runoff or by soil erosion to freshwater).